Analisis Strategi Dakwah di Era Digital: Studi Kasus : Akun Instagram Ust. Hanan Attaki - Lala Nabilah Chandra; Yunia Rahmiati; Faiz Abdurrahman; Abiyyu Haidar Mutawakkil; M. Faruq Al-Barqi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The da'wah strategy carried out by Ust. Hanan Attaki on Instagram includes several important aspects, such as content form, communication style, and audience engagement. The da'wah content delivered is not only normative and rigid, but rather more on the storytelling approach that inspires many people. The communication style used is straightforward, relaxed, and close to the everyday language of urban teenagers. Consistency and frequency in delivering da'wah messages are very important in maintaining audience engagement. Ust. Hanan Attaki actively uploads content at least 3-5 times a week, which has built an important presence in maintaining audience engagement. Interactivity is also the main advantage of social media compared to conventional media. Ust. Hanan Attaki utilizes the comments, live, and Q&A features on his Instagram to interact directly with his followers. Overall, Ust. Hanan Attaki's da'wah strategy has shown an effort to harmonize Islamic religious values ​​and the growing digital culture. The content delivered is not only theological, but also touches on the psychological and social aspects of teenagers.